Malmquist Productivity Index on Efficiency Layers - F. Rezai balf ∗; M. Hatef (Journal of Mathematical Extension, 2012)
Data Envelopment Analysis (DEA), a popular linear programming technique is useful to rate comparatively operational effiency of decision Making Unit (DMU) based on the their deterministic inputoutput data. The Malmquist productivity index in DEA, calculable with the distance function, for measurement the productivity change among two variant time period or two variant group in the same time. This index is based on two factor of efficiency change index and a technological change index. In this paper, we operate on the collective Malmquist productivity index, which performs clustering operation DMUs with classification into different levels of efficient frontier, and then we discuss on the relation between Malmquist index on the efficiency layers and their attractiveness and progress